PENGARUH KETERLIBATAN PELANGGAN, KUALITAS LAYANAN, CITRA MEREK DAN PENGALAMAN MEREK TERHADAP KEPUASAN PELANGGAN PADA PENGGUNA TRANSPORTASI ONLINE DI DKI JAKARTA - Dwi Atmoko, Yudi; Riorini, Sri Vandayuli; Hidasanita, Helzya; Tahira, Nina (Business, Economics dan Entrepreneurship, 2024)
The research aims to find out how influential customer involvement, the quality of service, the brand image and brand experience of customer satisfaction on online transport users. This study is aimed at grab, one of southeast Asia's transportation services. The data collection on this research USES field research by spreading "questionnaire" to 200 user responders at grab application in dki Jakarta, as well as the library research by reviewing from a journal and other structures related to the study. Regression analysis and correlation are used for information screening. The result of this research suggests that the involvement of the customer, quality services, brands' and brands' experience on the satisfaction of the online transport's customers in dki dki will be particularly significant in the development of grab loyalty at the Jakarta stock exchange. This suggests that variable customer satisfaction can be explained by variable customer reliability, service satisfaction, brand image, brand experience of 61 percent.. The rest of the 39 percent is explained by other factors not included in this research model. The effect of some of the influences with the satisfaction of the customer can be illustrated by the regression equation obtained by the positive signed coefficient value of regression, which suggests that both the quality of service and the price have a positive impact.